Analyzing the Adaptation of Ramayana Wayang Characters in Code Atma Video Game - Ariel Marsha Luana Brahmana; Banung Grahita (Universitas Multimedia Nusantara, 2023)
Promotion of Wayang is important for future generations to continue cherish the value, meaning and pure passion just like how it is intended to be. As a traditional culture surviving the modern era, a modern adaptation is one of the many ways to promote towards the younger generations alongside other modern pastimes. The game “Code Atma” developed by Agate in 2020 has attracted the younger generation due to its appealing character design, that is a modern rendition to what is familiar, traditional culture. To ensure focus of the research, the chosen Code Atma characters would be the ones from Ramayana story: Shinta, Rama, Rahwana, and Hanuman. This qualitative research uses the comparative analysis to group and breakdown further the elements of a character, namely visual aspect, personality, and skills of each Code Atma characters to the original Ramayana Wayang Kulit characters. The essential elements of each character are presented by analyzing the similarities using the Jungian Archetypes by Carl Jung. There are limits in redesigning a Wayang character for a modern adaptation, because posture, proportion, and clothing are core elements that must remain to keep the character’s identity recognizable. Keywords: adaptation; archetype; character; game